Investigation of tribological layers with time-of-flight secondary ion mass spectrometry (Tof-sims) additive’s influence on friction behavior of wet multi-plate clutches Analyse tribologischer schichten mit der flugzeitsekundärionenmassenspektrometrie (Tof-sims) additiveinflüsse auf das reibungsverhalten nasslaufender lamellenkupplungen - Stockinger, U.; Völkel, K.; Pflaum, H.; Stahl, K.; Mühlenstrodt, K.; Lipinsky, D.; Arlinghaus, H. F. (VDI Berichte, 2019)
The friction behavior of wet multi-plate clutches cannot be determined theoretically, because of complex physical and chemical interactions between the components. Therefore, experiments are required. Friction measurements of power shifts in combination with surface analysis with Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS) were performed to correlate friction behavior and composition of the boundary layer. The friction behavior was analyzed for paper type friction linings and lubricants of a known composition on the component test rig ZF/FZG KLP-260 at different combinations of surface pressure and sliding velocity. ToF-SIMS was used to characterise the boundary layers of tribologically stressed plate surfaces. An established database of additive characteristic signals was used to determine their lateral and depth-dependent composition. Chemical interactions between the various combinations of base oils and their additive treatment give rise to differences in the tribological boundary layers. This, in turn, influences the corresponding friction behavior. When using pure base stock, the type of base stock significantly influences the friction behavior. For the fully formulated lubricant (base stock + additive package), the friction behavior of the three different base stocks was similar. The surface analysis confirmed a similar boundary layer composition when the friction behavior was comparable.
CRIS-Team Scopus Importer:2025-05-19